The Impact of Students' Perceptions at the University of Bangka Belitung (UBB) on Hybrid Learning Toward Digital Workforce Readiness in the Post-COVID-19 Pandemic Era - Mumtaz, Keisya Taqiyya Abrara Mumtaz; Rizal, Debby Belpa; Rachmadhy, Dhevan; Wijaya, Eric Lindra; Putra, Agung Rizki (Lembaga Riset, Publikasi dan Konsultasi JONHARIONO, 2025)
This study analyzes the perceptions of Bangka Belitung University students towards hybrid learning and its impact on digital work readiness post-COVID-19 pandemic. Results show that positive perceptions have a significant effect on digital readiness (β = 0.338; p < 0.001; R² = 22.4%). Time flexibility is valued, but digital infrastructure is a barrier. Students are adaptive to technology, but competitiveness in the job market needs to be improved. The findings emphasize the need to strengthen digital